2015
DOI: 10.1515/hf-2014-0286
|View full text |Cite
|
Sign up to set email alerts
|

Determination of log moisture content using ground penetrating radar (GPR). Part 1. Partial least squares (PLS) method

Abstract: Ground penetrating radar (GPR) is a handheld system showing good potential for the real-time and nondestructive characterization of wood moisture content (MC). However, measurements performed over logs can be challenging because of their curved surface that can affect the GPR signal. In this study, the MC of thawed and frozen logs was estimated for three species (quaking aspen, balsam poplar, and black spruce) using the full GPR signals and the partial least squares (PLS) regression method. The signal was acqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The log samples and the data sets are identical with those described in Part 1 ( Hans et al 2015 ). The two-way travel time t t (ns) of the GPR signal through the log can be computed as the diff erence between the arrival times of the direct and refl ected waves of the GPR traces.…”
Section: Methodsmentioning
confidence: 99%
“…The log samples and the data sets are identical with those described in Part 1 ( Hans et al 2015 ). The two-way travel time t t (ns) of the GPR signal through the log can be computed as the diff erence between the arrival times of the direct and refl ected waves of the GPR traces.…”
Section: Methodsmentioning
confidence: 99%
“…In this case, data from all four drying stages were used (model group 1). Models were also created to estimate log diameter and bark thickness from GPR signals (model group 3) since previous studies suggested that log diameter is highly correlated to GPR signals [23].…”
Section: Response Variables Covariate Variables and Time Window Selec...mentioning
confidence: 99%